Production process of waterproof wear-resistant silica gel for mobile phone card holder

By adding modified epoxy resin and modified boron nitride whiskers to the silicone material for mobile phone trays, the existing mobile phone trays have been solved, and silicone materials with excellent mechanical properties, waterproof properties and wear resistance are prepared to meet the needs of high-performance mobile phone trays.

CN119798998APending Publication Date: 2025-04-11DONGGUAN JIANBANG ELECTRONICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411924539.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing mobile phone trays have problems in terms of unstable waterproof performance, insufficient wear resistance, low dimensional accuracy and difficult surface treatment, and cannot fully meet the market's demand for high-performance and high-reliability mobile phone trays.

Method used

A production process of waterproof and wear-resistant silicone for mobile phone trays is adopted. The raw materials include liquid silicone, modified epoxy resin, modified boron nitride whiskers, fluorosilicone oil, silane coupling agent, platinum catalyst and inhibitor. Silicone materials with excellent waterproof and wear-resistant properties are prepared by stirring and vacuum defoaming.

Benefits of technology

It significantly improves the mechanical properties, waterproof performance and wear resistance of the product. It is suitable for high-demand mobile phone tray application scenarios, and provides more reliable and durable mobile phone accessories.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005208906740000091
    Figure BDA0005208906740000091
  • Figure BDA0005208906740000101
    Figure BDA0005208906740000101
  • Figure BDA0005208906740000102
    Figure BDA0005208906740000102
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer material preparation, and particularly relates to a production process of waterproof wear-resistant silica gel for a mobile phone card holder. The formula of the waterproof wear-resistant silica gel comprises 100 parts of liquid silica gel, 20-40 parts of modified epoxy resin, 10-15 parts of modified boron nitride whiskers, 2-5 parts of fluorosilicone oil, 1-3 parts of a silane coupling agent, 0.1-0.5 part of a platinum catalyst and 0.02-0.1 part of an inhibitor. The production process comprises the steps of mixing, stirring, vacuum defoaming and the like. According to the production process disclosed by the invention, through formula optimization and modification treatment, the mechanical property, water resistance and wear resistance of the silica gel are remarkably improved, and the silica gel is suitable for high-requirement application scenes such as mobile phone card holders.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer material preparation, and in particular relates to a production process of waterproof and wear-resistant silica gel for a mobile phone card tray. Background Art

[0002] With the popularity of smart phones and the diversification of usage environments, users have put forward higher requirements for the durability and protection of mobile phones and their accessories. As one of the important components inside the mobile phone, the mobile phone card tray not only needs to have good mechanical properties to ensure the stable installation of the SIM card or memory card, but also needs to have certain waterproof and dustproof capabilities to protect the internal circuit from the influence of the external environment.

[0003] Traditional mobile phone card holders are mostly made of metal or plastic, which can meet the basic usage requirements of mobile phones to a certain extent. However, as consumers' requirements for mobile phone functions and appearance design continue to increase, the limitations of traditional materials are gradually emerging. For example, although metal card holders are strong, they are prone to rust when exposed to moisture, which affects their service life; and although plastic card holders are low-cost, they have poor wear resistance and water resistance, and are prone to deformation or damage after long-term use.

[0004] In recent years, in order to overcome the shortcomings of the above materials, some manufacturers have begun to try to use silicone materials to make mobile phone card trays. As a new type of material, silicone has attracted widespread attention due to its excellent physical and chemical properties (such as good elasticity and temperature resistance). Especially in terms of waterproof and wear resistance, silicone has shown significant advantages. Silicone itself has good hydrophobicity and can effectively prevent moisture penetration, thereby protecting the internal circuit of the mobile phone from the influence of humid environment. Silicone has high hardness and toughness, and it is not easy to wear or deform even when the SIM card or memory card is frequently inserted and removed. Silicone is not easy to become brittle at low temperatures and is not easy to soften at high temperatures. It can maintain good performance in a wide temperature range. Silicone materials are non-toxic and harmless, friendly to the human body and the environment, and in line with modern consumption trends.

[0005] Although silicone materials have shown many advantages in the application of mobile phone card trays, existing silicone mobile phone card trays still face some challenges in actual use:

[0006] 1. Unstable waterproof performance: After long-term use, the waterproof layer of some silicone card holders may age or fall off, resulting in a decrease in waterproof performance.

[0007] 2. Insufficient wear resistance: Although silicone has good wear resistance, it may still be worn or scratched under extreme conditions (such as frequent plugging and unplugging or contact with sharp objects).

[0008] 3. Low dimensional accuracy: Silicone materials tend to shrink during the curing process, resulting in low dimensional accuracy of the finished product, affecting the compatibility of the card tray with the mobile phone.

[0009] 4. Difficulty in surface treatment: The surface treatment of silicone materials is difficult, and it is difficult to achieve a smooth and delicate effect, which affects the appearance of the product.

[0010] In summary, the existing mobile phone card trays still cannot fully meet the market demand for high-performance and high-reliability mobile phone card trays. Therefore, developing a production process for waterproof and wear-resistant silicone for mobile phone card trays that can effectively solve the above problems has important practical significance and broad application prospects. Summary of the invention

[0011] The purpose of the present invention is to provide a production process of waterproof and wear-resistant silica gel for mobile phone card trays, which can effectively solve the defects in the prior art, produce mobile phone card trays with excellent waterproof and wear-resistant properties, and provide users with more reliable and durable mobile phone accessories.

[0012] In order to achieve the above object, the present invention provides the following technical solutions:

[0013] A production process of waterproof and wear-resistant silica gel for mobile phone card holders. The raw materials thereof include the following components by mass: 100 parts of liquid silica gel, 20-40 parts of modified epoxy resin, 10-15 parts of modified boron nitride whiskers, 2-5 parts of fluorosilicone oil, 1-3 parts of silane coupling agent, 0.1-0.5 parts of platinum catalyst and 0.02-0.1 parts of inhibitor.

[0014] The production process comprises the following steps:

[0015] (1) Add liquid silica gel into a mixer, stir and evenly disperse;

[0016] (2) adding modified epoxy resin, silane coupling agent, platinum catalyst and inhibitor, and continuing to stir to fully mix the components;

[0017] (3) Add fluorosilicone oil and continue stirring to evenly disperse the fluorosilicone oil;

[0018] (4) adding modified boron nitride whiskers, reducing the rotation speed, and continuing stirring to obtain a mixture;

[0019] (5) vacuum degassing the mixture obtained in step (4) to obtain the waterproof and wear-resistant silica gel.

[0020] Furthermore, in step (1), the rotation speed of the mixer is set to 1000-1500 rpm, and the stirring time is 10-15 minutes.

[0021] Furthermore, the stirring time in step (2) is 15-20 minutes.

[0022] Furthermore, the stirring time in step (3) is 10-15 minutes.

[0023] Furthermore, in step (4), the rotation speed is reduced to 500-800 rpm, and the stirring time is 10-15 minutes.

[0024] Furthermore, the preparation method of the modified epoxy resin comprises the following steps:

[0025] (a) adding epoxy resin into a reaction vessel, adding monomer solution during stirring, and continuing stirring for 20-40 minutes, wherein the monomers are butyl acrylate and acrylic acid;

[0026] (b) adding an initiator and continuing stirring for 10-15 minutes to obtain a mixture, wherein the initiator is benzoyl peroxide;

[0027] (c) transferring the mixture into a preheated reactor, setting the reaction temperature to 60-80° C. and the reaction time to 2-4 hours;

[0028] (d) After the reaction is completed, the reactant is cooled to room temperature, and the reactant is ground to select a particle size within the range of 1-5 μm to obtain a modified epoxy resin.

[0029] Furthermore, the monomer solution is an ethanol solution containing 10-20 wt % of butyl acrylate and 2-5 wt % of acrylic acid.

[0030] Furthermore, the molar ratio of the epoxy resin to the monomer is 1:(1.5-3).

[0031] Furthermore, the mass of the initiator is 0.5-2% of the mass of the epoxy resin.

[0032] The present invention adds modified epoxy resin in the formula. The introduction of butyl acrylate and acrylic acid enables the epoxy resin to form more crosslinking points during the curing process, thereby enhancing the stability of the network structure. The long-chain structure of butyl acrylate gives the epoxy resin higher flexibility, making it less likely to crack when subjected to external stress, thereby significantly improving the mechanical strength of the material. The long-chain alkyl in butyl acrylate is hydrophobic, which can enhance the hydrophobicity of the epoxy resin and improve the waterproof effect. The introduction of acrylic acid increases the rigidity of the epoxy resin, making it less likely to deform during the friction process, thereby improving the wear resistance.

[0033] Furthermore, the preparation method of the modified boron nitride whisker comprises the following steps:

[0034] (i) dissolving dopamine hydrochloride in a Tris-HCl buffer solution to prepare a dopamine solution, and dissolving PEG (polyethylene glycol) in deionized water to prepare a dispersant solution;

[0035] (ii) adding boron nitride whiskers to a dispersant solution, heating the solution to 60-80° C., and performing a dispersion treatment using a disperser to ensure that the boron nitride whiskers are evenly dispersed to obtain a boron nitride whisker suspension;

[0036] (iii) adding the boron nitride whisker suspension to the dopamine solution and stirring for 1-2 hours to allow dopamine to polymerize on the surface of the boron nitride whiskers to form polydopamine;

[0037] (iv) After the reaction is completed, the reactant is filtered, washed with deionized water, dried, and ground to collect modified boron nitride whiskers with a particle size in the range of 1-5 μm.

[0038] Furthermore, in step (i), the pH value of the Tris-HCl buffer solution is 8-8.5, the concentration of the dopamine solution is (0.8-2) g / 100 mL, and the concentration of the dispersant solution is 0.5-1 wt %.

[0039] Furthermore, the particle size of the boron nitride whisker is 1-3 μm, the length is 10-50 μm, the mass ratio of the boron nitride whisker to dopamine hydrochloride is (5-10):1, and the mass volume ratio of the boron nitride whisker to the dispersant solution is (5-10) g / 100 mL.

[0040] Boron nitride whiskers have high modulus and high strength. As a reinforcing phase, they can significantly improve the mechanical strength and toughness of silicone. The whiskers form a microstructure in the silicone matrix, effectively transferring and dispersing external stress and preventing crack propagation caused by stress concentration. The high hardness and wear resistance of boron nitride whiskers can significantly improve the wear resistance of silicone and reduce wear under extreme conditions. The presence of whiskers can form a physical barrier, reduce friction contact points, and reduce wear rate. Dopamine surface modification improves the compatibility and dispersibility of boron nitride whiskers with the silicone matrix, further enhancing the wear resistance.

[0041] Furthermore, the silane coupling agent is selected from one or more of vinyl trimethoxy silane, trimethylethoxy silane, γ-methacryloxypropyl trimethoxy silane, γ-aminopropyl triethoxy silane, and γ-glycidyloxypropyl trimethoxy silane.

[0042] Furthermore, the platinum catalyst is a chloroplatinic acid catalyst, and the Pt content is 1000-20000ppm.

[0043] Furthermore, the inhibitor is ethynyl cyclohexanol.

[0044] The present invention selects liquid silicone as the base material, and liquid silicone can bring excellent mechanical strength, elasticity and temperature resistance to the product. The modified epoxy resin forms a stable three-dimensional network structure through a cross-linking reaction, which significantly improves the mechanical strength and elastic modulus. Boron nitride whiskers are used as a reinforcing phase to further improve the mechanical strength and toughness, and the two work together to make the silicone more stable when subjected to external stress. The long-chain alkyl in the modified epoxy resin is hydrophobic, which enhances the hydrophobic properties of the epoxy resin. The fluorocarbon chain in the fluorosilicone oil has an extremely low surface energy, forming a hydrophobic film, further improving the waterproof performance. The rigidity of the modified epoxy resin and the high hardness of the boron nitride whiskers jointly improve the wear resistance of the silicone. The presence of whiskers can form a physical barrier, reduce friction contact points, and reduce the wear rate. Fluorosilicone oil improves the lubricity of the silicone surface, reduces friction, and further improves the wear resistance. The low surface tension can also reduce the adhesion of dust and particulate matter, further reducing wear. Silane coupling agent can enhance the bonding force between the silica gel matrix and the filler, reduce the water penetration path, improve the waterproof effect, and reduce the fall-off of the filler during wear, thereby improving the wear resistance. The present invention significantly improves the mechanical properties, waterproof properties and wear resistance of the product through reasonable formula design and the synergistic effect of each component.

[0045] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0046] The present invention adopts reasonable formula design and synergistic effect of various components, so that the prepared silicone material has excellent mechanical properties and waterproof properties, and is suitable for high-demand application scenarios such as mobile phone card trays. DETAILED DESCRIPTION

[0047] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] The raw materials used in the examples are all common commercially available products, and the following is an exemplary description:

[0049] Liquid silicone was purchased from Dow Corning, DC 3140;

[0050] Epoxy resin purchased from Huntsman, EPIKOTE TM Resin 828;

[0051] PEG (polyethylene glycol) was purchased from Shandong Jinyueyuan New Materials Co., Ltd., PEG-2000;

[0052] Chloroplatinic acid isopropanol solution was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., C10040;

[0053] Ethynyl cyclohexanol was purchased from Shandong Luxi Chemical Co., Ltd., LC-100;

[0054] Fluorosilicone oil was purchased from Beijing Fluorochemical Industry Co., Ltd., FSL-1000;

[0055] Methyl silicone oil was purchased from Tianjin Shuangjixing Technology Co., Ltd., SGX-M1000;

[0056] Boron nitride whiskers were purchased from Shandong Luyang Energy Saving Materials Co., Ltd., BNW-100;

[0057] Basalt fiber was purchased from Jiangsu Tianlong Basalt Continuous Fiber Co., Ltd., TL-1000, with a fiber diameter of 10-20 μm.

[0058] Example 1

[0059] The present embodiment provides a production process of waterproof and wear-resistant silica gel for mobile phone card trays, wherein the raw materials include the following components by mass: 100 parts of liquid silica gel, 30 parts of modified epoxy resin, 13 parts of modified boron nitride whiskers, 3 parts of fluorosilicone oil, 2 parts of silane coupling agent (vinyl trimethoxy silane), 0.2 parts of platinum catalyst (chloroplatinic acid isopropanol solution, Pt content is 1000ppm), and 0.05 parts of inhibitor (ethynyl cyclohexanol);

[0060] The production process comprises the following steps:

[0061] (1) Add liquid silica gel into a mixer, set the speed to 1200 rpm, and stir for 15 minutes to make it evenly dispersed;

[0062] (2) adding modified epoxy resin, silane coupling agent, platinum catalyst and inhibitor, and continuing stirring for 18 minutes to fully mix the components;

[0063] (3) Add fluorosilicone oil and continue stirring for 12 minutes to evenly disperse the fluorosilicone oil;

[0064] (4) adding modified boron nitride whiskers, reducing the rotation speed to 500-800 rpm, and continuing stirring for 12 minutes to obtain a mixture;

[0065] (5) The mixture obtained in step (4) is subjected to vacuum degassing at a vacuum degree of -0.1 MPa for 15 minutes to obtain the waterproof and wear-resistant silica gel.

[0066] The preparation method of the modified epoxy resin comprises the following steps:

[0067] (a) adding epoxy resin to a reaction vessel, adding a monomer solution during stirring, wherein the monomer solution is an ethanol solution containing 15 wt % butyl acrylate and 3 wt % acrylic acid, and continuing stirring for 30 minutes, wherein the molar ratio of epoxy resin to monomer is 1:2;

[0068] (b) adding 1% by weight of the epoxy resin as an initiator, benzoyl peroxide, and continuing stirring for 15 minutes to obtain a mixture;

[0069] (c) transferring the mixture into a preheated reactor, setting the reaction temperature to 70° C. and the reaction time to 3 hours;

[0070] (d) After the reaction is completed, the reactant is cooled to room temperature, and the reactant is ground to select a particle size within the range of 1-5 μm to obtain a modified epoxy resin.

[0071] The preparation method of the modified boron nitride whisker comprises the following steps:

[0072] (i) dissolving dopamine hydrochloride in a Tris-HCl buffer solution with a pH value of 8 at a mass volume ratio of 1 g / 100 mL to prepare a dopamine solution, and dissolving PEG in deionized water to prepare a 0.8 wt % dispersant solution;

[0073] (ii) adding boron nitride whiskers to a dispersant solution, wherein the mass volume ratio of boron nitride whiskers to dispersant solution is 7 g / 100 mL, heating to 60-80° C., and performing a dispersion treatment using a high-speed disperser to ensure that the boron nitride whiskers are uniformly dispersed to obtain a boron nitride whisker suspension;

[0074] (iii) adding the boron nitride whisker suspension to the dopamine solution, with the mass ratio of boron nitride whisker to dopamine hydrochloride being 7:1, and stirring for 1.5 hours to allow dopamine to polymerize on the surface of the boron nitride whisker to form polydopamine;

[0075] (iv) After the reaction is completed, the reactant is filtered, washed with deionized water, dried, and ground to collect modified boron nitride whiskers with a particle size in the range of 1-5 μm.

[0076] Example 2

[0077] This embodiment provides a production process of waterproof and wear-resistant silica gel for mobile phone card holders, which is different from the embodiment 1 in that the raw materials include the following components by mass: 100 parts of liquid silica gel, 22 parts of modified epoxy resin, 10 parts of modified boron nitride whiskers, 5 parts of fluorosilicone oil, 2 parts of silane coupling agent (vinyl trimethoxy silane), 0.2 parts of platinum catalyst (chloroplatinic acid isopropanol solution, Pt content is 10000ppm), and 0.05 parts of inhibitor (ethynyl cyclohexanol). The rest is the same as the embodiment 1.

[0078] Comparative Example 1

[0079] This comparative example provides a production process of waterproof and wear-resistant silica gel for mobile phone card holders, which is different from Example 1 in that the raw materials include the following components by mass: 100 parts of liquid silica gel, 50 parts of modified epoxy resin, 13 parts of modified boron nitride whiskers, 3 parts of fluorosilicone oil, 2 parts of silane coupling agent (vinyl trimethoxy silane), 0.2 parts of platinum catalyst (chloroplatinic acid isopropanol solution, Pt content is 10000ppm), and 0.05 parts of inhibitor (ethynyl cyclohexanol). The rest is the same as Example 1.

[0080] Comparative Example 2

[0081] This comparative example provides a production process of waterproof and wear-resistant silica gel for mobile phone card trays, which differs from Example 1 in that an epoxy resin of equal mass is used to replace the modified epoxy resin.

[0082] Comparative Example 3

[0083] This comparative example provides a production process of waterproof and wear-resistant silica gel for mobile phone card trays, which differs from Example 1 in that boron nitride whiskers of equal mass are used to replace modified boron nitride whiskers.

[0084] Comparative Example 4

[0085] This comparative example provides a production process of waterproof and wear-resistant silica gel for mobile phone card trays, which differs from Example 1 in that modified boron nitride whiskers are replaced with basalt fibers.

[0086] Comparative Example 5

[0087] This comparative example provides a production process of waterproof and wear-resistant silicone for mobile phone card trays, which differs from Example 1 in that fluorosilicone oil is replaced by methyl silicone oil.

[0088] Performance test 1 Mechanical properties test

[0089] According to GB / T528-2009 “Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber”, the tensile strength and elongation at break of the silicone rubber prepared in Examples 1-2 and Comparative Examples 1-5 were tested.

[0090] The wear amount of the silica gel prepared in Examples 1-2 and Comparative Examples 1-5 was tested according to the test method specified in GB / T 9867-2008 "Determination of wear resistance of vulcanized rubber or thermoplastic rubber".

[0091] The results are shown in Table 1.

[0092] Table 1 Strength, elongation and abrasion

[0093]

[0094]

[0095] It can be seen from the above performance test results that the silica gel prepared in Examples 1 and 2 of the present invention has excellent tensile strength, elongation at break and wear resistance. The excessive amount of modified epoxy resin used in Comparative Example 1 leads to a decrease in the flexibility of the material, and the mechanical strength and wear resistance are affected. Comparative Example 2 uses unmodified epoxy resin, which lacks functional groups and cannot effectively improve the mechanical strength and wear resistance, resulting in a decrease in overall performance. Comparative Example 3 uses unmodified boron nitride whiskers, which lack surface modification treatment, resulting in poor compatibility and dispersibility with the silica gel matrix, affecting the mechanical strength and wear resistance. Comparative Example 4 replaces the modified boron nitride whiskers with basalt fibers. The hardness and wear resistance of basalt fibers are not as good as those of boron nitride whiskers, resulting in a significant decrease in mechanical strength and wear resistance. Comparative Example 5 replaces fluorosilicone oil with methyl silicone oil. The hydrophobicity of methyl silicone oil is not as good as that of fluorosilicone oil, which has a certain effect on wear resistance.

[0096] Performance test 2 Waterproof test

[0097] The silica gel prepared in Examples 1-2 and Comparative Examples 1-5 was used as the test sample. The samples were cut into flat slices with a size of 2 cm×2 cm. The initial weight of the sample was weighed W0. The sample was completely immersed in deionized water for 24 hours. The sample was taken out of the water, and the surface moisture was gently absorbed with filter paper. The final weight of the sample was weighed W0. f , calculate the water absorption rate: Water absorption rate = (W f -W0) / W0×100%.

[0098] The results are shown in Table 2.

[0099] Table 2 Water absorption

[0100]

[0101]

[0102] It can be seen from the above performance test results that the silica gel prepared by the present invention has excellent waterproof performance. Comparative Example 2 uses unmodified epoxy resin, which lacks functional groups and cannot form an effective hydrophobic layer, resulting in poor hydrophobicity; in addition, the unmodified epoxy resin has a low crosslinking density, resulting in insufficient density of the material, which is easy to allow moisture to penetrate. Comparative Example 5 replaces fluorosilicone oil with methyl silicone oil. The fluorocarbon chain in fluorosilicone oil has extremely low surface energy and excellent hydrophobic properties. Although the methyl chain in methyl silicone oil also has a certain hydrophobicity, it is not as strong as the fluorocarbon chain.

[0103] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A production process of waterproof and wear-resistant silica gel for mobile phone card holders, wherein the raw materials include the following components by mass: 100 parts of liquid silica gel, 20-40 parts of modified epoxy resin, 10-15 parts of modified boron nitride whiskers, 2-5 parts of fluorosilicone oil, 1-3 parts of silane coupling agent, 0.1-0.5 parts of platinum catalyst, and 0.02-0.1 parts of inhibitor; The production process comprises the following steps: (1) Add liquid silica gel into a mixer, stir and evenly disperse; (2) adding modified epoxy resin, silane coupling agent, platinum catalyst and inhibitor, and continuing to stir to fully mix the components; (3) Add fluorosilicone oil and continue stirring to evenly disperse the fluorosilicone oil; (4) adding modified boron nitride whiskers, reducing the rotation speed, and continuing stirring to obtain a mixture; (5) vacuum degassing the mixture obtained in step (4) to obtain the waterproof and wear-resistant silica gel.

2. The production process according to claim 1, characterized in that: In step (1), the speed of the mixer is set to 1000-1500 rpm, and the stirring time is 10-15 minutes; in step (2), the stirring time is 15-20 minutes; in step (3), the stirring time is 10-15 minutes; in step (4), the speed is reduced to 500-800 rpm, and the stirring time is 10-15 minutes.

3. The production process according to claim 1, characterized in that: The preparation method of the modified epoxy resin comprises the following steps: (a) adding epoxy resin into a reaction vessel, adding monomer solution during stirring, and continuing stirring for 20-40 minutes, wherein the monomers are butyl acrylate and acrylic acid; (b) adding an initiator and continuing stirring for 10-15 minutes to obtain a mixture, wherein the initiator is benzoyl peroxide; (c) transferring the mixture into a preheated reactor, setting the reaction temperature to 60-80° C. and the reaction time to 2-4 hours; (d) After the reaction is completed, the reactant is cooled to room temperature, and the reactant is ground to select a particle size within the range of 1-5 μm to obtain a modified epoxy resin.

4. The production process according to claim 3, characterized in that: The monomer solution is an ethanol solution containing 10-20 wt % of butyl acrylate and 2-5 wt % of acrylic acid.

5. The production process according to claim 3, characterized in that: The molar ratio of the epoxy resin to the monomer is 1:(1.5-3).

6. The production process according to claim 3, characterized in that: The mass of the initiator is 0.5-2% of the mass of the epoxy resin.

7. The production process according to claim 1, characterized in that: The preparation method of the modified boron nitride whisker comprises the following steps: (i) dissolving dopamine hydrochloride in a Tris-HCl buffer solution to prepare a dopamine solution, and dissolving PEG in deionized water to prepare a dispersant solution; (ii) adding boron nitride whiskers to a dispersant solution, heating the solution to 60-80° C., and performing a dispersion treatment using a disperser to uniformly disperse the boron nitride whiskers to obtain a boron nitride whisker suspension; (iii) adding the boron nitride whisker suspension to the dopamine solution and stirring for 1-2 hours to allow dopamine to polymerize on the surface of the boron nitride whiskers to form polydopamine; (iv) After the reaction is completed, the reactant is filtered, washed with deionized water, dried, and ground to collect modified boron nitride whiskers with a particle size in the range of 1-5 μm.

8. The production process according to claim 7, characterized in that: The pH value of the Tris-HCl buffer solution in step (i) is 8-8.5, the concentration of the dopamine solution is (0.8-2) g / 100 mL, and the concentration of the dispersant solution is 0.5-1 wt %.

9. The production process according to claim 7, characterized in that: The particle size of the boron nitride whisker is 1-3 μm, the length is 10-50 μm, the mass ratio of the boron nitride whisker to dopamine hydrochloride is (5-10):1, and the mass volume ratio of the boron nitride whisker to the dispersant solution is (5-10) g / 100 mL.

10. The production process according to claim 1, characterized in that: The silane coupling agent is selected from one or more of vinyl trimethoxysilane, trimethylethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-aminopropyl triethoxysilane, and γ-glycidyloxypropyl trimethoxysilane; the platinum catalyst is a chloroplatinic acid catalyst with a Pt content of 1000-20000ppm; and the inhibitor is ethynyl cyclohexanol.